ANALISIS HUKUM SYARIAH DALAM IMPLEMENTASI HUKUMAN CAMBUK DI INDONESIA - Enden Haetami (Globalwriting Academica Consulting & Publishing, 2020)
The caning punishment carried out in Aceh Province is a punishment that is carried out quite openly in a public place, and is easy for various groups of people to witness, including children. The purpose of this research is to see how the caning punishment is implemented in Aceh. This research will be carried out using a qualitative approach. The data used in this study comes from the results of previous studies that discuss similar matters. The results of this study found that the defendants who were undergoing this punishment were not necessarily deterred. In the following years, several cases such as drunkenness and gambling have the potential to recur. This is because there is no rehabilitation mechanism in the sentence. Then many children also watched the caning.